Human Resource Development in Higher Education: A Humanistic Core–AI Enhanced Model from Islamic Perspectives - Ummu Shofiyah; Ali Muhtarom (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Human resource development (HRD) is a strategic factor in ensuring the sustainability and competitiveness of higher education institutions amid globalization, digital transformation, and the rapid advancement of artificial intelligence (AI). This study aims to examine the evolution of HRD management, identify dominant HRD models, and analyze future challenges and opportunities in higher education from both contemporary and Islamic perspectives. A Systematic Literature Review (SLR) was conducted using articles published between 2016 and 2026. Literature searches were performed through Publish or Perish across Scopus, Web of Science, and Google Scholar, and analyzed using the PRISMA 2020 framework. A total of 674 records were identified, of which 50 articles met the eligibility criteria for the final review. The findings reveal a shift from conventional administrative HRD toward strategic, adaptive, and technology-enabled management. The review identifies several dominant models, including Strategic Human Resource Management (SHRM), Organizational Citizenship Behavior (OCB), Knowledge Transfer-Based HRD, Career Ecosystem-Based HRD, and AI-based HRD. As its primary theoretical contribution, this study proposes the Humanistic Core–AI Enhanced Human Resource Development (HCAE-HRD) model, which integrates SHRM, OCB, and AI-Driven HRD while positioning humanistic values as the core and AI as a supporting tool. From an Islamic perspective, the model is strengthened by the principles of amanah, ihsan, ta'awun, adl, and shura, providing an ethical and sustainable framework for human resource development in higher education.